2016
DOI: 10.1016/j.celrep.2016.06.070
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of TRIM25 Catalytic Activation in the Antiviral RIG-I Pathway

Abstract: SUMMARY Antiviral response pathways induce interferon by higher-order assembly of signaling complexes called signalosomes. Assembly of the RIG-I signalosome is regulated by K63-linked polyubiquitin chains, which are synthesized by the E3 ubiquitin ligase, TRIM25. We have previously shown that the TRIM25 coiled-coil domain is a stable, antiparallel dimer that positions two catalytic RING domains on opposite ends of an elongated rod. We now show that the RING domain is a separate self-association motif that enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
171
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(181 citation statements)
references
References 53 publications
(112 reference statements)
9
171
1
Order By: Relevance
“…TRIM25 is widely accepted as a positive regulator of RIG‐I signaling, with numerous studies, including our own, describing its regulation of RIG‐I response to viral infection and/or its interaction with RIG‐I . The data presented here clearly show that in two human epithelial cell lines and in primary mouse fibroblasts, TRIM25 is not required for a physiological RIG‐I‐mediated immune response to influenza virus infection.…”
Section: Discussionmentioning
confidence: 73%
“…TRIM25 is widely accepted as a positive regulator of RIG‐I signaling, with numerous studies, including our own, describing its regulation of RIG‐I response to viral infection and/or its interaction with RIG‐I . The data presented here clearly show that in two human epithelial cell lines and in primary mouse fibroblasts, TRIM25 is not required for a physiological RIG‐I‐mediated immune response to influenza virus infection.…”
Section: Discussionmentioning
confidence: 73%
“…Two subunits pack in an anti‐parallel manner, forming an elongated rod‐shaped scaffold with a RING domain on each end; the two RING domains are separated by 17–20 nm and so cannot directly interact with each other. On the other hand, other studies have shown that the isolated RING domains of TRIM5α, TRIM25, and TRIM32 engage E2–Ub conjugates and catalyze Ub conjugation as close‐packed dimers . Taken together, these observations imply that the catalytically active form of TRIMs comprises at least two coiled‐coil mediated dimers (four protein molecules).…”
Section: Introductionmentioning
confidence: 84%
“…4A). Bacterially expressed Flag-tagged NZAP protein was incubated with purified proteins that are required for ubiquitination, including ubiquitin, Uba1 (E1), an E2 complex for TRIM25 Uev1a-Ubc13 (38,39), and TRIM25. The resulting NZAP proteins were detected by Western blotting with an anti-Flag antibody.…”
Section: Resultsmentioning
confidence: 99%